Characterization of an Acrylamide-degrading Bacterium Isolated from Hydrocarbon Sludge (Bioremediation Science and Technology Research (e-ISSN 2289-5892), 2019)
A major source of acrylamide in soil comes from herbicide formulation that contained polyacrylamide that slowly decomposes to acrylamide. Research in acrylamide biodegradation by microbe as a tool for its bioremediation is slowly gaining attention globally. In this research, a hydrocarbon-degrading Pseudomonas sp. strain Dr Y Kertih isolated from petroleum sludge was able to grow on acrylamide. The results show that 1% (w/v) glucose supplied with acrylamide (as the only nitrogen source) was the best carbon source for the growth of acrylamide-degrading bacterium. The isolate was also able to use diesel as a carbon source. The bacterium shows an optimal growth at 300 mg/L acrylamide, pH between pH 6.5 and 7.5 and temperature between 25 and 30 Â°C. The isolate was able to grow on amides such as acetamide and 2-chloroacetamide, but their growth was inhibited by toxic heavy metals such as mercury, cadmium and chromium. Growth kinetic studies using the Haldane model for growth indicated substrate toxicity at higher concentrations on acrylamide. The maximum growth rate (Âµmax) was 0.267 h-1 while the saturation constant or half velocity constant Ks and inhibition constant Ki, were 0.182 and 0.25 g/L, respectively. Thus, the bacterium holds great potential as a candidate to remediate acrylamide.
Keywords: Acrylamide; Pseudomonas; acrylamide-degrading; growth kinetics; Haldane